Pyramidal Stereogenic Nitrogen Centers (SNCs) - Zaitseva, Snizhana; Köhler, Valentin (Synthesis, 2024)
The configuration at a stereogenic nitrogen center (SNC) determines the spatial organization of a molecule as do stereogenic carbon centers or other stereochemical moieties. The contributions of SNCs to molecular function and their consideration in molecular design are rarely prominently presented. Underlying is the configurational lability of SNCs with a free electron pair and the scarcity of methods for the stereoselective synthesis of compounds with SNCs in general. In this review, we discuss methods to access compounds with configurationally stable SNCs and highlight some of the synthetically most relevant applications. We hope to draw attention to the potential of this stereochemical feature that can be present in diverse compounds such as N-oxides, oxaziridines, haloamines, ammonium ions, metal-bound amines, and constrained amines and amides.1 Introduction2 Some Historical Notes3 Factors That Influence The Nitrogen Inversion Barrier4 Preparation and Isolation of Compounds with Configurationally Stable Stereogenic Nitrogen Centers5 Selected Applications of Compounds with Stereogenic Nitrogen Centers6 Final Remarks
Keywords: stereoselective synthesis; nitrogen; chirality; cations; amines; N-oxides